Studying the influence of uv adsorbers on optical characteristics of light-protective polymer films for textile materials - Olga Semeshko (Eastern-European Journal of Enterprise Technologies, 2019)
The use of UV adsorbers included in composition of a polymer film is a promising way of color protecting against effects of light since application of the polymer to the textile material surface is a universal way of providing the textile materials with necessary special properties.